2005
DOI: 10.1159/000084315
|View full text |Cite
|
Sign up to set email alerts
|

Anseriform Brain and Its Parts versus Taxonomic and Ecological Categories

Abstract: The size of the brain and its macro-anatomical parts in 206 birds representing 19 anseriform species and 4 tribes (Anserini, Anatini, Aythyini and Mergini) was the subject of a comparative analysis. The comparisons involved two aspects: taxonomic (differences among species within tribes and differences among tribes) and ecological (diet composition: vegetation, invertebrates, or fish and the foraging mode: browsing, dabbling, shallow diving, and deep diving). The relative size of the encephalon (E) and its par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 79 publications
2
14
0
1
Order By: Relevance
“…Of the three internal organs of the goosander studied, liver weight showed the largest variability, the coefficient of variation being few to several (depending on the group) times higher than the CV of kidney and brain weights. This finding confirms observations of other authors dealing with anseriform morpho-anatomy (Drobney 1984;Kalisińska 2005;Kalisińska et al 1999). The goosander liver weight accounts, on the average, for 3.4% of the body weight and is similar to that (2.5-3.5%) of the shallow diving ducks of the genus Aythya (Austin and Fredrickson 1987;Gammonley and Heitmeyer 1990).…”
Section: Discussionsupporting
confidence: 92%
“…Of the three internal organs of the goosander studied, liver weight showed the largest variability, the coefficient of variation being few to several (depending on the group) times higher than the CV of kidney and brain weights. This finding confirms observations of other authors dealing with anseriform morpho-anatomy (Drobney 1984;Kalisińska 2005;Kalisińska et al 1999). The goosander liver weight accounts, on the average, for 3.4% of the body weight and is similar to that (2.5-3.5%) of the shallow diving ducks of the genus Aythya (Austin and Fredrickson 1987;Gammonley and Heitmeyer 1990).…”
Section: Discussionsupporting
confidence: 92%
“…Behavioral studies indicate that vision is more critical in some species than in others [Tome and Wrubleski, 1988] and there is some interspecific variation in eye movements and visual field within the order [Martin, 1986;Guilleman et al, 2002;Martin et al, 2007a]. Kalisinska [2005] reported that the optic lobes were larger in piscivorous and diving ducks than in other species and we did detect some variation in the relative size of the TeO and nRt among the species we sampled. Based on the apparent correlations among retinal morphology, tectofugal and thalamofugal brain region volumes and behavior in owls, we predict that waterfowl likely share with owls enhanced scotopic vision, but relatively poor color discrimination and visual acuity.…”
Section: Discussionmentioning
confidence: 53%
“…Ecological factors appear to influence brain evolution in diverse taxa, for example diet correlates with brain size in fishes, bats, primates and birds (Hutcheon et al 2002;Kalisinska 2005;Dunbar & Shultz 2007;Yopak et al 2007). A species' habitat also poses specific cognitive challenges related to either navigation or spatial orientation (Salas et al 2003;Safi & Dechmann 2005;Pollen et al 2007;Yopak et al 2007).…”
Section: Introductionmentioning
confidence: 99%